Instagram As Media and Tool in English Language Teaching - Ary Putra Sanusi; Dea Serly Safitri; Surahmi Sabar (State Islamic Institute of Bone, Indonesia, 2021)
The main concern of this paper is to discuss the use of Instagram features as a media and tool in English language teaching. This paper outline the points including Social Media for Education and Instagram for English Language Teaching. The discussion of this paper reports that Instagram is beneficial for the English language teaching where there are several features which can support the teacher to conduct an effective and efficient teaching and learning process. It also supported by some technical use com combining digital media of Instagram and English language materials. The content of this paper is also expected to contribute for the teacher to make a digital learning environment through the media and tool that provided by Instagram.Keywords: Instagram, Media, Tool, English Language Teaching